Exploring the impact of FinTech on sustainable development in Malaysia: an interpretative phenomenological analysis - Masrina Nadia Mohd Salleh; Shaliza Alwi; Herwina Rosnan; Norwazli Abdul Wahab (Discover Sustainability)
Abstract This study explores the cognitive and motivational factors influencing the innovative behaviors of Malaysian FinTech entrepreneurs and their contributions to the Sustainable Development Goals (SDGs), particularly in financial inclusion and economic growth. Using Interpretative Phenomenological Analysis (IPA), it examines the lived experiences of five entrepreneurs through semi-structured interviews and thematic analysis. The findings highlight how cognitive and affective factors shape decision-making, resilience, and adaptability in a rapidly evolving industry. This research links FinTech entrepreneurship to SDG 8 (Decent Work and Economic Growth), SDG 9 (Industry, Innovation, and Infrastructure), and SDG 10 (Reduced Inequality), underscoring its role in financial accessibility and sustainable development. It fills a gap in the literature by examining internal cognitive factors that drive innovation. The insights provide policymakers, educators, and industry stakeholders with strategies to foster a supportive FinTech ecosystem. Future research should explore the interactions between technology, regulations, and entrepreneurship, as well as cultural and regional differences. Longitudinal studies could track evolving cognitive and motivational influences. Examining global trends such as AI, blockchain, digital currencies, and ESG integration may further illuminate sustainable growth opportunities in Malaysia’s FinTech sector.